Pengembangan Pemasaran Abon Ikan Bandeng Laut Produksi Usaha Mikro “Dpore Meme” Desa Alasmalang, Kecamatan Panarukan, Kabupaten Situbondo - Rizal; Nila Viva Rahman (Jurnal Suara Pengabdian 45, 2023)
The strategic marine and fisheries potential of Situbondo Regency includes a high (106.28 tonnes per year) potential for catching sea milkfish (Chanos chanos). The neighborhood makes very little attempts to use processed sea milkfish, nevertheless. Fishermen on the Situbondo coast catch sea milkfish (Chanos chanos), which is only sold fresh and has a poor selling price. Using this chance, Dpore Meme Micro Business turns fresh marine milkfish into shredded fish with a great nutritious value. Because it has a unique flavor, a softer texture, is more fragrant and delectable, and is packed with nutrients, marine milk floss has a potential commercial opportunity and is highly alluring to the general population. There is a need for marketing development, which includes developing online marketing, expanding the marketing area, increasing collaboration with marketing networks or resellers in areas outside the city of Situbondo, as well as optimizing promotions to support product marketing. The current challenge is that the marketing and promotion carried out by the Dpore Meme Micro Enterprise is still offline and on a local scale in the Situbondo Regency area.